2017
DOI: 10.1002/ange.201700570
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasma Membrane Ceramides by Super‐Resolution Microscopy

Abstract: The sphingolipid ceramide regulates cellular processes such as differentiation, proliferation, growth arrest and apoptosis. Ceramide-rich membrane areas promote structural changes within the plasma membrane which segregates membrane receptors and affect membrane curvature and vesicle formation, fusion and trafficking. Here, we label ceramides by immunocytochemistry and visualize their distribution on the plasma membrane of different cells with virtually molecular resolution by direct stochastic optical reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Considering the fluidity of the cell membrane, we used fixed HeLa cells to observe the distribution of GLUT1. When the fixation was not adequate, proteins on cell membranes would not be completely immobilized, causing the redistribution of proteins (32,33). So, we first optimized the fixation time and found that the morphology of GLUT1 has no significant difference on cell membranes with different fixation time (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the fluidity of the cell membrane, we used fixed HeLa cells to observe the distribution of GLUT1. When the fixation was not adequate, proteins on cell membranes would not be completely immobilized, causing the redistribution of proteins (32,33). So, we first optimized the fixation time and found that the morphology of GLUT1 has no significant difference on cell membranes with different fixation time (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was shared with many other laboratories to determine the intracellular distribution of ceramide and was instrumental to our research on ceramide-enriched compartments (CECs) (18-21, 25, 27). Most recently, this antibody allowed the visualization of ceramide rafts using superresolution microscopy (dSTORM) (18), clearly demonstrating that the distribution of ceramide in cellular membranes is anisotropic and regulated by SMase(s).…”
Section: Discussionmentioning
confidence: 99%
“…Increase of ceramide levels through upregulation of CerSs or SMases leads to induction of apoptosis and other cell signaling pathways critical for cell death, senescence, autophagy, or cell cycle arrest. We and others showed that the localized generation or distribution of ceramide in ceramide microdomains (rafts) or more extended ceramide-enriched compartments (CECs) may have additional cellular functions of ceramide (16)(17)(18)(19)(20)(21)(22)(23). Instrumental to our studies was the generation of a ceramide-specific antibody originally developed in our laboratory (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dihydroceramide desaturase (DES); ceramidase (CDase); sphingomyelin synthase (SMS); glucosylceramide synthase (GCS); glucosylceramidase (GCase); ceramide galactosyltransferase (CGT); galactosylceramidase (GalC). direct stochastic optical reconstruction microscopy found that between 50% and 60% of all ceramide in the plasma membrane localize in CRPs (5). Ceramide-mediated clustering of Fas receptor (CD95) at the plasma membrane was found to be essential for formation of death-inducing signaling complex and subsequent caspase activation (6).…”
Section: Ceramide Membrane Dynamicsmentioning
confidence: 99%